Targeted Drone Killings Under International Human Rights Law - جميل حسن يونس; الجنابي هديل صالح (Journal of Legal Sciences, 2021)
Targeted killings by unmanned aircraft are a dangerous means that threaten the human right to life, both in wartime and in peacetime. In wartime, international humanitarian law prohibits weapons that cannot respect general principles such as discrimination, proportionality and military necessities. In peacetime, all international instruments guaranteeing the protection of human rights prohibit attacks on the right to life, except in cases provided for by law, as well as extrajudicial executions.